ERGONOMICS AND THERMOGRAPHY INSIDE THE ASSEMBLY LINE (Fiep Bulletin - online, 2017)
This research was developed in a Brazilian assembler and discusses the use of infrared imaging technology calledthermography in the occupational environment is still very incipient condition. Presents a comparative approach to traditionalergonomic analysis tools, OWAS, New Checklist of Couto and RULA, applied to upper limbs and infrared imaging method.Discusses the generation of heat in the human body due to static or dynamic postural requirements, specifically in the muscles as anobject for study thermography. Explanations are given on the thermographic technology and their physical settings, as well as themethodology applied and the characteristics and parameters of the equipment used. Traditional ergonomic tools used in thisresearch are detailed the method and setting are described. Complemented by field research, the study found that traditionalergonomic analysis methods differ from each other, even when it comes exclusively from the upper limbs, making it difficult to applyin isolation, that is, the survey revealed that should apply more than a tool to get success and above all, depend on the knowledgeand experience of the evaluator. Therefore, the thermographic method is recommended as quantitative complementary tool for thevalidation of information from other traditional methods.